ANALISIS TITIK PULANG POKOK USAHA VIRGIN COCONUT OIL (VCO) PADA UKM PENGAIS JAYA DI DESA AMPIBABO KECAMATAN AMPIBABO KABUPATEN PARIGI MOUTONG - syam, Nur; M., Marhawati; Alam, Max Nur (AGROTEKBIS, 2013)
Plantation commodities that are capable of supporting the establishment of some industries are coconut trees (Cocos nucifera L). Coconut has a broad usability as a raw material for other than food and non food industries as well as household consumption. Utilization of coconu not only as coconut oil but there are several other coconut products sale in the international trade market, such as grated coconut, fresh coconut, coconut charcoal, coconut sugar and coconut oil known as Virgin Coconut Oil (VCO). The purpose of this study was to analyze: (i) the total cost of production, (ii) the amount of physical production, (iii) the selling price, and (iv) the amount of revenue that the UKM pengais Jaya Virgin Coconut Oil (VCO) received, so business can achieve break-even point. The study location and sampling was determined by intentionally (purposive) by the leaders of UKM PengaisJaya Virgin Coconut Oil scavengers in the Ampibabovillage. The analytical tool used in this research was the analysis of break-even point. The results showed that the highest break-even point achieved at the product Virgin Coconut Oil (VCO) obtained from the sale of product for 1000 ml bottle was Rp. 4,121,007, or approximately 50.64 %, on the second level obtained in bottles of 500 ml equal to Rp 2,409,605 or approximately 29.61 %, and the smallest revenue obtained in the packaging of 250 ml, only of Rp . 1,606,40 or approximately 19.74%.